Kata Pinjaman Bahasa Arab dalam Bahasa Minangkabau - Zikrawahyuni Maiza (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2017)
Minangkabau language is one of influenced languages of South East Asian region, which are subject to influence and characterization by influencing languages that are the medium of dissemination of cultures and believes. Of the influential languages is Arabic, medium of dissemination of Islam. As Minangkabau people embrace Islam, they also embrace and get familiar with Arabic, and adapt Arabic words according to the norms of Minangkabau language. Thus, this research is intended to identify loan words in Minangkabau language that can be traced back to Arabic language, and analyze the changes made to the words. The loan words are compared to the original words of Arabic language to identify the changes, and analyze the meanings, forms and phoneme. This research is library research that comprises data collection and analysis methods. The samples for this research are the loan words taken from Kamus Umum Bahasa Minangkabau Indonesia. Besides, al-Mucjam al-Wasit is used to trace the original meanings in Arabic language whereas Kamus Kontemporer Arab Indonesia is significant to identify the translated meanings in Indonesian language. This research shows that there is an interaction between the Arabians and the people of Minangkabau, leaving a positive effect in enriching Minangkabau language with Arabic loan words. The loan words can be classified: as loan word with sustained meanings and loan words with changed meanings according to word-meaning relation; as loan words with sustained form and loan words with changed form according to alphabetical form; as loan words with sustained pronunciation and loan words with changed pronunciation according pronunciation aspect. However, most Arabic loan words in Minangkabau language retain meaning originality and word form but there are few loan words are subject to changes in meaning and form.